Teises keeles õppimine: Tartu muu kodukeelega lastevanemate vaade - Birute Klaas-Lang; Kristiina Praakli; Diana Vender (Eesti Rakenduslingvistika Ühingu Aastaraamat)
Artikkel käsitleb Tartu muu emakeelega lastevanemate vaadet eesti keeles õppele. Autorid viisid 2023. aastal kahes Tartu üldhariduskoolis läbi kvalitatiivse uuringu eesmärgiga kaardistada lastevanemate küsimusi ja murekohti eestikeelsele haridusele ülemineku protsessis. Teoreetiline raamistik toetub rahvusvahelistele uuringutele vanemate hoiakute ja arusaamade mõjust laste õppimisele teises keeles. Uuringu tulemused näitavad, et suur osa Tartu vene kodukeelega vanematest peab oluliseks eesti- ja venekeelsete õpilaste edaspidist hariduse omandamist kõigile ühises kooliruumis ja eesti keeles. Vanemate arvates on aga üleminekul palju väljakutseid, sh hariduse kvaliteedi võimalik langus eesti keelt ja ainesisu valdavate pedagoogilise pädevusega õpetajate puuduse tõttu; laste koormuse kasv ja stress mitte-emakeelses õppes; sobivate õppematerjalide puudumine; vanemate suutmatus last eesti keele vähese oskuse tõttu kodutöödes aidata; laste kaugenemine omakultuurist; eesti keeles õppimiseks vajaliku motivatsiooni vähesus. *** "Learning in a second language: The attitudes of parents with non-Estonian first language in Tartu" *** From September 1, 2024, Estonia started the transition to Estonian-language education, with the aim of ending the dual Estonian and Russian school system that was established during the Soviet occupation and lasted after Estonia regained independence in 1991. In 2023, the authors conducted a qualitative study based on discussion evenings (n = 4, with 250 parents) at two bilingual schools in Tartu. The study explores parents’ (L1 non-Estonian) views on the transition, highlighting positive aspects, challenges, concerns, and their beliefs about second-language acquisition and their role in the process. Data was drawn from researchers’ diary notes documenting these discussions. The theoretical framework focuses on how parents’ attitudes affect children’s learning in a second language. Parents’ opinions on the transition to Estonian-language education vary. While some see positive aspects, however, there are also those who oppose it, as well as parents who are confused and concerned. Furthermore, parents worry that their children will distance themselves from their mother tongue and culture due to Estonian-language education. Parents are concerned about the potential decline in their children’s education quality. They fear that learning in a second language will reduce their children’s subject knowledge and academic performance. Parents feel responsible for their children’s academic results but are concerned that they won’t be able to help their children with schoolwork, as their own Estonian skills may not be sufficient. They also question school personnel policies, which the parents think prioritize Estonian language proficiency but don’t account for teachers’ experience in managing linguistic diversity and multilingual classrooms. However, during the discussion evenings, parents made several suggestions to reduce their fears about the transition to Estonian-language education. They believe children with different mother tongues should study together in the same school, and that all-day school programs and joint activities with Estonian speaking kids outside of school are needed. Support should also be provided for teaching the mother tongue and culture to children who do not speak Estonian.